COMPLEX THERAPY IMPACT ON THE QUALITY OF LIFE OF CHILDREN WITH ALLERGIC RHINITIS - A.Yu. Tomilova; L.S. Namazova; L.M. Kuzenkova; O.I. Maslova; A.M. Mamed"yarov (Педиатрическая фармакология)
This article is dedicated to the burning issue, which is the impact of the long term treatment for allergic rhinitis on the quality of life of patients and their family members. It was uncovered that practically all the children, suffering from allergic rhinitis, experienced certain phenomena of the social deadaptation and decreased quality of life. in the meantime, the adequate anti-inflammatory therapy for the acute allergic rhinitis is conducive to better quality of life of children and their family members, while the prescription of a cognitive nootrop — hopantenic acid together with the basic anti-inflammatory therapy for the all year allergic rhinitis by means of mometasone much more efficiently improves the quality of life of children, suffering from persistent allergic rhinitis.Key words: allergic rhinitis, children, hopantenic acid, mometasone, treatment.